OPTIMALISASI MANAJEMEN TRAFIK DAN KEAMANAN DATA PADA JARINGAN INTRANET IBI-K 1957 DENGAN METODE USER BEHAVIOUR ANALYSIS - Hidayat, Syamsu; Astried Silvanie; ASISTYASARI, AYUNI; Nuryaman, Yosep (STMIK KAPUTAMA, 2023)
The incident of a data breach at one of the national banks as a result of the merger of several Islamic banks in Indonesia for economic reasons has significantly increased concerns about the security of the data of all organizations, including educational organizations such as universities, where there are such as a personal data system and also educational data for the academic community, the open internet sharing systems enabled by universities are highly vulnerable to cyber attacks. For this reason, an optimization measure for the security of the campus network was implemented in this study and, in addition, the Internet connection was made more stable, as it is perceived as very slow at certain hours or during working hours. The use of Mikrotik as a network security tool designed to establish a network security fortress against intruders. In addition to the fact that Mikrotik devices are easy to obtain and inexpensive, and have good security features, the use of the method of analyzing user behavior consists in using a firewall to detect users who download activities with certain criteria are recorded and marked by the firewall , to then restrict access for the user. The. In addition to utilizing Mikrotik's firewall capabilities, the Queue feature is also used with the Simple Queue and Queue Tree methods. In the Simple Queue method, it designates one of the hosts whose bandwidth is limited, while in Queue Tree, it limits the network segments that provide users with maximum bandwidth limits and guarantees bandwidth. Both can be used side by side and work optimally.